Analisa Strategi E-Marketing dan Implementasinya pada Rental Company - Meyliana Meyliana (Binus Business Review, 2011)
Customers are the main key for persistence of a company. The company could arrange old customers and attract new customers, as marketing event. Marketing is one component in customer relationship management. Marketing today has become a trend in doing promotion, increase new customers to expand target market, and maintain old customer loyalty to increase the company sales’ point volume. Supported by appropriate information technology, marketing event could be changed as events that give benefit to the company. Marketing event with information technology, e-marketing, is done to increase company image. After being analysed, this e-marketing strategy will be implemented to rental company.